Effects of pomegranate juice on blood pressure: A systematic review and meta-analysis of randomized controlled trials. (January 2017) - Sahebkar, Amirhossein; Ferri, Claudio; Giorgini, Paolo; Bo, Simona; Nachtigal, Petr; Grassi, Davide
Graphical abstract: Abstract: Punica granatum L. (Pomegranate) has been claimed to provide several health benefits. Pomegranate juice is a polyphenol-rich fruit juice with high antioxidant capacity. Several studies suggested that pomegranate juice can exert antiatherogenic, antioxidant, antihypertensive, and anti-inflammatory effects. Nevertheless, the potential cardioprotective benefits of pomegranate juice deserve further clinical investigation. To systematically review and meta-analyze available evidence from randomized placebo-controlled trials (RCTs) investigating the effects of pomegranate juice consumption and blood pressure (BP). A comprehensive literature search in Medline and Scopus was carried out to identify eligible RCTs. A meta-analysis of eligible studies was performed using a random-effects model. Quality assessment, sensitivity analysisand publication bias evaluations were conducted using standard methods. Quantitative data synthesis from 8 RCTs showed significant reductions in both systolic [weighed mean difference (WMD): −4.96 mmHg, 95% CI: −7.67 to −2.25, p < 0.001) and diastolic BP (WMD: −2.01 mmHg, 95% CI: −3.71 to −0.31, p = 0.021) after pomegranate juice consumption. Effects on SBP remained stable to sensitivity analyses. Pomegranate juice reduced SBP regardless of the duration (>12 wks: WMD = −4.36 mmHg, 95% CI: −7.89 to −0.82, p = 0.016) and <12 wks: WMD = −5.83 mmHg, 95% CI: −10.05 to −1.61, p = 0.007) and dose consumed (>240 cc: WMD = −3.62 mmHg, 95% CI: −6.62 to −0.63, p = 0.018) and <240 cc: WMD = −11.01 mmHg, 95% CI: −17.38 to −4.65, p = 0.001, pomegranate juice per day) whereas doses >240 cc provided a borderline significant effect in reducing DBP. The present meta-analysis suggests consistent benefits of pomegranate juice consumption on BP. This evidence suggests it may be prudent to include this fruit juice in a heart-healthy diet.